Pancreatic neuroendocrine microadenomatosis: A case report of cytology and histology correlation. Issue 2 (27th September 2016) - Vo, Nguyen; Cohen, David W.; Dillhoff, Mary E.; Jin, Ming
Abstract : Pancreatic neuroendocrine neoplasia is categorized by grade, size, and functional status. Neuroendocrine microadenoma (NEMA) is defined as a neuroendocrine tumor (NET) that measures less than 0.5 cm in diameter. Multiple NEMAs are termed neuroendocrine adenomatosis (NEMAtosis). The surgical pathology and clinical aspects of pancreatic NEMAtosis have been reported, but there has been no report regarding EUS‐FNA cytology of NEMAtosis. We report a case of NEMAtosis with cytologic correlation and illustrate the diagnostic challenges and potential pitfalls. The pre‐operative cytology can be problematic. The main differential diagnosis of the EUS‐FNA specimen includes NET, normal pancreas, and islet cell hyperplasia/aggregation associated with chronic pancreatitis. The helpful cytopathologic feature of NEMAtosis is the presence of two intermingled populations of loosely‐cohesive neuroendocrine cell clusters and tight acinar cell groups arranged in microacinar and/or grape‐like structures. Although neuroendocrine cells and acinar cells possess different cytomorphology, the distinction is not always straightforward because both types of cells are small and cytologically bland. Cytologic assessment of both architecture and individual cell morphology is imperative to avoid interpretation error and further guide appropriate clinical management. Diagn. Cytopathol. 2017;45:143–147. © 2016 Wiley Periodicals, Inc.